THE TECHNICAL OPERATING PARAMETERS OF REMOTE SENSING FOR THE ASK MONITORING OF LAND RESOURCES - Гебрин, Л. В. (Ukrainian journal of remote sensing, 2014)
The systems generate and disseminate data for operational monitoring. A comparative analysis of the technical parameters ofcosmic pressure washer that are most commonly used to assess the conduct of monitoring of land resources. Highlight the problemsolved with the help of data space sounding. The relationship of the selection of the optimal set of the system depending on thepurpose of the task.